Mrežno povezovanje družbenih gibanj in (ne)možnosti emancipatoričnega komuniciranja - Sekloča, Peter (Družboslovne razprave, 2016)
The authors present various forms of social movements and discuss common points on which the movements have built their positions towards the authorities and the media, and raise the question of how a supposedly democratic network structure of movements can build a coalition to face the dominant power (of the authorities and the media). The possibility of maintaining the heterogeneity of positions and identities is thematised through the distinction between "collective" and "connecting action", as conceptualised by the modern theory of digital citizenship as activism, the foundation of which represents a network society. In the foreground is the verification of the thesis that some specifics of the connecting action, which are formed at the intersection of communication and organisational practices, strengthen the emancipation of movements and their potential to create new policies and new ways of parallel exchange.
Keywords: Družbena gibanja; Social movements; Protesti; Protests; Elektronski mediji; Digital media; Communication; Komuniciranje; Slovenia; Slovenija; mreženje; vstaje